Transition to a mesenchymal state in neuroblastoma may be characterized by a high expression of GD2 and by the acquisition of immune escape from NK cells - Di Matteo, Sabina; Bilotta, Maria Teresa; Pelosi, Andrea; Haas, Dorothee; Theinert, Tobias; Weber, Gerrit; Schlegel, Paul-Gerhardt; Berg, Matthias; Moretta, Lorenzo; Maggi, Enrico; Azzarone, Bruno; Vacca, Paola; et al. (Frontiers in Immunology, 2024)
Background. Neuroblastoma (NB) is characterized by both adrenergic (ADRN) and undifferentiated mesenchymal (MES) subsets. The ganglioside sialic acid-containing glycosphingolipid (GD2) is widely overexpressed on tumors of neuroectodermal origin promoting malignant phenotypes. The MES cells are greatly enriched in post-therapy and relapsing tumors and are characterized by decreased expression of GD2. This event may cause the failure of GD2-based immunotherapy. NK cells represent a key innate cell subset able to efficiently kill tumors. However, the tumor microenvironment (TME) that includes tumor cells and tumor-associated (TA) cells could inhibit their effector function. Methods. We studied 8 NB primary cultures that, in comparison with commercial cell lines, more faithfully reflect the tumor cell characteristics. We studied four primary NB-MES cell cultures and two pairs of MES/ADRN (691 and 717) primary cultures, derived from the same patient. In particular, in the six human NB primary cultures, we assessed their phenotype, the expression of GD2 and the enzymes that control its expression, as well as their interactions with NK cells, using flow cytometry, RT-qPCR, and cytotoxicity assays. Results. We identified mature (CD105+/CD133-) and undifferentiated (CD133+/CD105-) NB subsets that express high levels of MES transcripts WWTR1 and SIX4. In addition, undifferentiated MES cells display a strong resistance to NK mediating killing. On the contrary, mature NB-MES cells display an intermediate resistance to NK-mediated killing and exhibit some immunomodulatory capacities on NK cells, but do not inhibit their cytolytic activity. Notably, independently from their undifferentiated or mature phenotype, NB-MES cells express GD2 that can be further up-regulated in undifferentiated NB-MES cells, upon co-culture with NK cells, leading to the generation of mature mesenchymal GD2bright neuroblasts. Concerning 691 and 717, they show high levels of GD2, and resistance to NK cell-mediated killing that can be overcome by the administration of dinutuximab beta, the anti-GD2 monoclonal antibody applied in the clinic. Conclusions. NB is a heterogeneous tumor representing a further hurdle in NB immunotherapy. However, differently from what was reported with NB commercial cells and independent of their MES/ADRN phenotype, maintained the expression of GD2 and displayed sensitivity to anti-GD2 mAb ADCC indicating a possible effectiveness of anti-GD2 immunotherapy.